2020
DOI: 10.3390/genes11101135
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Fusarium graminearum-Responsive lncRNAs in Triticum aestivum

Abstract: Although the war between wheat and Fusarium has been widely investigated for years, long noncoding RNAs (lncRNAs), which have been proven to regulate important processes in the development and stress responses of plants, are still poorly known in wheat against Fusarium. Herein, we systematically reveal the roles of wheat lncRNAs in the process of Fusarium graminearum infection by high-throughput RNA sequencing. Well over 4130 of the total 4276 differentially expressed lncRNAs were already specifically expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The recommended conditions for PCR were used as follows: 95 °C for 10 min, followed by 40 cycles of 95 °C for 30 s, 58 °C for 30 s, and 72 °C for 30 s. All reactions were performed in triplicate for each sample. The relative expression analysis of each gene were calculated using the 2 −ΔΔCT method ( Duan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The recommended conditions for PCR were used as follows: 95 °C for 10 min, followed by 40 cycles of 95 °C for 30 s, 58 °C for 30 s, and 72 °C for 30 s. All reactions were performed in triplicate for each sample. The relative expression analysis of each gene were calculated using the 2 −ΔΔCT method ( Duan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism involved in mycotoxin toxicity includes lncRNA. , Several studies have found that exposure to aflatoxin B 1 (AFB 1 ) changes the expression of lncRNA and promotes the development of hepatotoxicity and cancer. OTA induces the overexpression of lncRNA in renal cell carcinoma and is related to cell death pathways and metabolism . The involvement of lncRNA in the regulation of mycotoxins is expected to become the focus of research because two lncRNAs (XLOC_302848 and XLOC_321638) are potential regulators of Fusarium head blight resistance . A recent study found that an lncRNA, lncRsp1, negatively regulated the expression of DON biosynthetic genes, TRI4 , TRI5 , TRI6 , and TRI13 , and the production of DON …”
Section: Long Noncoding Rna and Micrornamentioning
confidence: 99%
“…34 The involvement of lncRNA in the regulation of mycotoxins is expected to become the focus of research because two lncRNAs (XLOC_302848 and XLOC_321638) are potential regulators of Fusarium head blight resistance. 35 A recent study found that an lncRNA, lncRsp1, negatively regulated the expression of DON biosynthetic genes, TRI4, TRI5, TRI6, and TRI13, and the production of DON. 13 As a class of endogenous noncoding small molecules, miRNA usually exists in animals, plants, and viruses and participates in the regulation of many physiological diseases, including apoptosis, differentiation, necrosis, and inflammation.…”
Section: Long Noncoding Rna and Micrornamentioning
confidence: 99%
“…LincRNA-Cox2 increases the expression of the neighboring gene prostaglandin-endoperoxide synthase (Ptgs2) through an enhancer RNA mechanism, contributing to prostaglandin biosynthesis [68]. Most studies use 10 kb or 100 kb upstream and downstream as the estimated range of lincRNA cis-target genes [69,70]. In addition, some lncRNAs bind with mRNAs to form dimers, thereby reducing mRNA expression [67].…”
Section: Prediction Of the Target Genes Of Lincrnasmentioning
confidence: 99%